The Role of Public Relations of Universitas Negeri Jakarta as a Communication Facilitator on Social Media Instagram @unj_official - Putri, Dinda Nabilahzahra; Safitri, Dini; Putri, Maulina Larasati (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to find out the role of public relations as a communication facilitator on Instagram @unj_official social media for information dissemination. In this case, public relations had an important role to be able to convey information so that it can be well received and fulfill the information needed by the public about the organization. Is based on one of the roles of public relations, namely as a communication facilitator for the organization and its public. This study uses a descriptive qualitative method because the author wants to provide an overview to be able to explain what happened. Data collection techniques using interviews, observation, and documentation. The results of this study are that the Public Relations of the Universitas Negeri Jakarta had a role in providing communication facilities between the Universitas Negeri Jakarta and the public through social media, but it is not optimal in answering questions from followers of the Instagram account @unj_official